2018
DOI: 10.21037/jtd.2018.05.72
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer in patients under 50: a SEER analysis

Abstract: EC patients under 50-year-old had distinctive clinicopathological characteristics compared with patients over 50-year-old. Despite more often presenting with stage III and IV disease, survival rates were better in the younger cohort. Prognostic factors for ECSS in patients under 50 differed from those in all age patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
6
13
0
Order By: Relevance
“…7,8 Our findings support previous studies that demonstrated advanced disease presentation in younger patients. 14,15,[17][18][19] Furthermore, results of our analysis demonstrated that the incidence of metastatic disease at diagnosis decreased with increasing age quartile. Use of age 50 years and 60 years as cutoffs demonstrated that the rate of distant disease was approximately 30% higher for younger patients in both analyses.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…7,8 Our findings support previous studies that demonstrated advanced disease presentation in younger patients. 14,15,[17][18][19] Furthermore, results of our analysis demonstrated that the incidence of metastatic disease at diagnosis decreased with increasing age quartile. Use of age 50 years and 60 years as cutoffs demonstrated that the rate of distant disease was approximately 30% higher for younger patients in both analyses.…”
Section: Discussionmentioning
confidence: 60%
“…14,15,17,23 Although some studies demonstrate improved 5-year overall survival among younger patients, others fail to replicate these findings. [14][15][16][17][18][19]23 In this series, patients aged less than 75 years had a similar rate of receiving any surgical therapy, although patients aged less than 65 years were more likely to receive aggressive treatment with induction therapy þ surgery than older patients. However, stratification by stage demonstrated that the magnitude of survival benefits among younger patients decreased with increasing stage.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations